Arshile Gorky. The Seeds of Memory - Zirani, Mosses (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Arshile Gorky, christened as Vostanik Atoyan, was born in Khorgom village near the city of Van in Western Armenia. In 1910, he moved with his family to Aygestan district of the city, where he continued his education. Arshile Gorky’s creative path can be divided into three phases: “Purity”, “Torments” and “Maturity”. The first period coincides with his life as a child growing up in his hometown, in the environment of innocence and purity, unaware of any hardships of life. Having barely crossed into adolescence, Gorky lived through and felt on his own skin the horrors and barbarities of the Genocide, from which his family suffered heavily. When he arrived in the Unites States in his very young years, he inevitably faced the harsh experience of adapting to a new environment, to the life he had to live from that time on against his will. Despite the grim reality, he unwaveringly continued his creative journey. Later on, in order to detach himself from the day-to-day worries, he returned to his roots and found refuge in reminiscences. Here is where, upon turning the “memory” into a fertile ground for creativity, he revived his past in his own time. As a result, his newer creations communicate methods of expression and messages, not yet manifested in the history of art in his time. Gorky’s life was untimely interrupted, yet he was a prolific artist, and his creations, often rueful, speak of regeneration, like Prometheus’ liver… On July 21, 1948, Arshile Gorky hanged himself, ending his life path on his own will. Աւազանի անունով, Ոստանիկ Ադոյեան, Արշիլ Կորքին ծնած է Արեւմտահայաստանի Խորգոմ գիւղը որ կը գտնուէր Վանայ լիճի ափին: Ան իր մօրը եւ երկու քոյրերուն հետ 1910-ին կը փոխադրուի Վան քաղաքի Այգեստան հայաշատ թաղամասը, ուր կը սորուի նաեւ՝ Գրաբար եւ կը ծանօթանայ հայկական մանրանկարչութեան: Ան իր ստեղծագործական կեանքը կը բաժնէ երեք շրջաններու, «Մաքրութիւն», «Տանջանք» եւ «Հասունութիւն»: Առաջինը իր ծննդավայրին մէջ ապրած մանկական ժամանակաշրջանն է, ուր երեխաները կ’ըլլան անմեղ, մաքուր ու յաճախ նոյնիսկ անհաղորդ կեանքի դժուարութիւններուն: Պատանեկան շրջանին հազիւ աչքերը բացած, Կորքի իր մորթին վրայ զգաց ցեղասպանութեան արհաւիրքն ու խժդժութիւնները ու... տառապեցաւ: Իսկ երբ արդէն երիտասարդ՝ հասաւ ԱՄՆ, նախ՝ զարնուելով ու յարմարուելով տիրող դաժան իրականութեան, ստեղծագործական կեանքը ակամայ շարունակեց դժուարին պայմաններու տակ: Յետոյ խուսափելու համար տանջալից առօրեայէն, սկսաւ վերադառնալ իր արմատներուն ու ապաստանիլ յիշողութեան մէջ: Հոս է, որ ան ստեղծագործական սերմի վերածելով «յիշողութիւնը», վերակենդանացուց իր անցեալը իր ժամանակին մէջ: Ու տուաւ այնպիսի ստեղծագործութիւններ, որոնք նոր խօսք եւ նոր արտայայտչաձեւ հաղորդեցին արուեստի պատմութեան: Կ’ունենայ տառապալից ստեղծագործական կեանք մը եւ որովհետեւ վերջին տարիներուն իր տառապանքները նման էին Պրոմեթեւսի շարունակուող ու վերանորագուող չարչարանքներուն, ան ինքզինք կը կախէ, կամովին վերջ տալով իր կեանքին... Аршил Горки (настоящее имя Востаник Атоян), родился в 1904 году в селе Хоргом провинции Ван Западной Армении. Творческий путь Аршила Горки можно условно разделить на три этапа: «Чистота», «Муки», «Зрелость». Первый период совпадает с его жизнью ребенком в родном городе, в атмосфере невинности и чистоты, неведения о тяготах жизни. Едва переступив порог отрочества, Горки пережил и почувствовал на собственной шкуре ужасы и зверства Геноцида, не пощадившего его семью. Переехав совсем юным в Соединенные Штаты, он неизбежно столкнулся с жестокими сторонами адаптирования к новой действительности, к жизни, вы-павшей на его долю не по его воле. Невзирая на мрачную действительность, он был настойчив в своих творческих исканиях. Со временем, чтоб отгородить себя от каждодневных треволнений, он мысленно обратился к своим корням и обрел душевный покой в воспоминаниях. Именно тогда, превратив «память» в плодо-родную почву для творчества, он оживил прошлое в современной ему реальности. В результате поисков, в своих новых работах он пришел к выразительным средствам, не наблюдавшимся до этого в истории искусства. Жизнь Аршила Горки прервалась безвременно, но его творения, нередко печальные, говорят о восстановлении… как печень Прометея… 21-го июля 1948 года Аршил Горки повесился, завершив жизненный путь по собственной воле.
Keywords: Art studies; Arshile Gorky